Sunburst Tangerine - Stephen H. Futch; L.K. Jackson (EDIS, 2018)
This document first published in Sep. 1993 is about Sunburst, the most widely grown commercial early Florida tangerine. It is a cross between the two citrus hybrids Robinson and Osceola. This cross was made in 1961 and was released for commercial use in 1979 by C. J. Hearn of the United States Department of Agriculture in Orlando.